Use of parenteral antimicrobials in very small hospitals in inner Brazil: patterns, determinants, and opportunities for interventions in developing countries - Giacomini, J. L. [UNESP]; Fortaleza, C. M. [UNESP] (Elsevier, 2017)
Much of healthcare in developing countries takes place in small hospitals. Little is known about the use of antimicrobials in those settings. We studied the 60-day use of parenteral antimicrobials in 48 hospitals with up to 50 beds in inner Brazil. The overall use was 242.0 defined daily doses per 100 admissions, and broad-spectrum agents accounted for 26.8%. The existence of local guidelines, educational measures and restrictive policies for antimicrobial prescriptions, as well as infection control and microbiology resources, were significantly associated with lesser use. Those findings point to possible interventions aimed at preventing antimicrobial over-use in developing countries.
Keywords: Antimicrobial stewardship; Antimicrobial use; Developing countries; Infection control; Small hospitals